Pengaruh Citra Merek dan Kualitas Produk Terhadap Kepuasan Pelanggan Serta Dampaknya Terhadap Loyalitas Pelanggan: (Survei Pada Pelanggan Restoran Pringsewu Pangandaran) - Irna Melinda; Ari Arisman; Depy Muhamad Pauzy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of brand image and product quality on customer satisfaction and customer loyalty (Survey of Pringsewu Pangandaran restaurant customers). The method used is a quantitative approach with the survey method. With a research sample of 100 customers of Pringsewu Pangandaran Restaurant. The data used is primary data. The analytical tool used in this research is path analysis using SPSS 26.0. The results showed that the brand image perceived by the customers of Pringsewu Pangandaran Restaurant had very good criteria. The product quality at Pringsewu Pangandaran Restaurant has very good assessment criteria. Customer Satisfaction Pringsewu Pangandaran Restaurant has very good assessment criteria. Customer Loyalty to Pringsewu Pangandaran Restaurant Customers has quite good criteria. Brand Image has a significant effect on Customer Satisfaction. Product quality has a significant effect on customer satisfaction. Brand Image on Customer Loyalty through Customer Satisfaction is significant, meaning that Customer Satisfaction is able to mediate the effect of Product Quality on Customer Loyalty. Product Quality on Customer Loyalty through Customer Satisfaction is significant, meaning that Customer Satisfaction is able to mediate the effect of Product Quality on Customer Loyalty to Pringsewu Pangandaran Restaurant Customers.